Internet of Things-Based Charity Box Security With Automatic Money Detection And Location Tracking - Anggraini, Nur Septi; Salamah, Irma; Aryanti, Aryanti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research designs and develops an Internet of Things (IoT)-based charity box security system aimed at improving transparency, security, and efficiency in the management of donation funds. The system integrates a TCS3200 color sensor to detect banknotes, a Neo-6M GPS module for real-time location tracking, and 4x4 keypad as PIN-based access security. The ESP32 microcontroller acts as the control center, and the Telegram Bot API is used to send notifications directly to the user when suspicious activity or device movement occurs. Additional features such as buzzers, speakers, and solenoid doorlocks function as warning systems and automatic locks to prevent unauthorized access. Test results show that all features work well, with a high success rate in money detection, accurate location tracking, and fast notification delivery. Despite limitations in the accuracy of detecting some banknotes due to the similarity of RGB values, the overall system proved to be reliable and has the potential to be implemented in public facilities or places of worship. Further developments could include integration with cloud storage, the addition of cameras for visual identification, and mobile applications for more interactive remote control and monitoring.